2011
DOI: 10.3732/ajb.1000335
|View full text |Cite
|
Sign up to set email alerts
|

Integration of vessel traits, wood density, and height in angiosperm shrubs and trees

Abstract: Differences in trait integration between growth forms suggest that evolution of growth form in some lineages might be associated with the degree of trait interrelation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 84 publications
7
53
0
1
Order By: Relevance
“…Higher specific gravity at the stem base could, in part, be explained by a lower vessel frequency and especially by smaller vessel diameters, as seen in the negative relationship between specific gravity and conduit diameter (Figure 7), a phenomenon which has also been reported in other studies (Fan et al, 2012;Martínez-Cabrera et al, 2011). As reported by Gartner (1995), the pattern of xylem density from the base to the top of stem depends mainly, but not always entirely, on the pattern found from pith to bark, essentially because the vertical profile reflects the simultaneous production of outer wood at the base, if a plant is old enough, and core wood at the top.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Higher specific gravity at the stem base could, in part, be explained by a lower vessel frequency and especially by smaller vessel diameters, as seen in the negative relationship between specific gravity and conduit diameter (Figure 7), a phenomenon which has also been reported in other studies (Fan et al, 2012;Martínez-Cabrera et al, 2011). As reported by Gartner (1995), the pattern of xylem density from the base to the top of stem depends mainly, but not always entirely, on the pattern found from pith to bark, essentially because the vertical profile reflects the simultaneous production of outer wood at the base, if a plant is old enough, and core wood at the top.…”
Section: Resultssupporting
confidence: 79%
“…Moreover, vessel diameter may be related to the biomechanical requirements of tree support to accommodate the self-weight of stem and crown (Niklas, 1992). Under these circumstances, larger and more frequent vessels would negatively impact wood density (Hoadley, 2000;Fan et al, 2012;Martínez-Cabrera et al, 2011). Since density is a good indicator of mechanical properties (Glass & Zelinka, 2010;Kretschmann, 2010), higher values in the base would have a positive impact on the strength of the tree.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to our expectation, we found no relationship between wood specific gravity and vascular traits at the branch level, suggesting no tradeoff between wood specific gravity and conduction capacity in branches. Our results differ from those of previous studies conducted at relatively small spatial scales that showed that stem wood specific gravity related to vessel and vessel lumen fractions (Baltzer et al ., ; Gleason et al ., ) and vascular traits (Ackerly, ; Preston et al ., ; Jacobsen et al ., ; Martinez‐Cabrera et al ., ; McCulloh et al ., ), but confirm those of recent studies conducted at transcontinental and global scales that found no such relationships between stem wood specific gravity and vascular traits (Martinez‐Cabrera et al ., ; Poorter et al ., ; Russo et al ., ; Zanne et al ., ; Fan et al ., ). Yet we found significant negative correlations between wood specific gravity and mean vessel area and mean vessel hydraulic diameter in roots.…”
Section: Discussionmentioning
confidence: 99%
“…The tradeoffs involved have led to two non‐mutually exclusive hypotheses: (1) wood specific gravity should decrease with increasing vessel fraction, vessel area and vessel density affecting the amount of lumen space in wood (Preston et al ., ); and (2) wood specific gravity should increase with increasing fiber fraction, because fiber has the thickest cell walls and hence contributes most to the wood matrix (Poorter et al ., ). A growing number of studies have tested these two hypotheses (Ackerly, ; Preston et al ., ; Jacobsen et al ., ; Zanne et al ., ; Martinez‐Cabrera et al ., ; Gleason et al ., ), but few studies have so far integrated all wood anatomical elements to explore their relative contribution to wood specific gravity (Jacobsen et al ., ; Pratt et al ., ; Martinez‐Cabrera et al ., ; Poorter et al ., ; Lens et al ., ). Additionally, few studies have investigated the relationship between wood specific gravity and wood anatomy in the hyper‐diverse tropical forests and these studies have been limited to a relatively small number of species (Baltzer et al ., ; Zhu & Cao, ; Poorter et al ., ; McCulloh et al ., ; Fan et al ., ; Worbes et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A higher performance in xylem recovery of cavitation‐vulnerable species was recently also detected in temperate tree species, indicating a general coordination between these two key parameters (Ogasa et al ). It should also be considered that differences in biomechanics can affect wood traits of different growth forms (Martínez‐Cabrera et al ), and shrubs can sacrifice single shoots and form new ones from the basal buds. Another aspect not included in the presented study but with potential impact on the hydraulic architecture is the clonal reproduction of the analyzed species.…”
Section: Discussionmentioning
confidence: 99%